Limitations of Correlation Analysis in Analyzing The Relationship of God's Close with His Servant - Anatansyah Ayomi Anandari (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2021)
Human relationship with God can be described by human weakness and desire to serve the greater one. Weak humans need a protector and a place to complain about all problems. Not infrequently the problems of crushing life, despair, loss of hope and so on cannot be resolved alone. A place to complain about all the problems of life, without Him humans may lose their direction and purpose in life. It has become human nature created by Allah SWT, for the purpose of worshiping God. The human relationship with God is as a servant, so humans are obliged to worship Allah throughout their lives, because everything that humans do will be accounted for in the future. Correlation analysis is a statistical tool that can be used to determine the degree of linear relationship between a variable and another variable. Correlation can be positive or negative. Correlation analysis can only explain one correlation value, when the r value is positive then the relationship is positive or when the r value is negative then the relationship is negative, the r value cannot be both. Where as in Islam, the relationship between Allah and His servants can be positive or negative.